Combining intratumoral Treg depletion with androgen deprivation therapy (ADT): preclinical activity in the Myc-CaP model. Issue 1 (April 2018) - Shen, Ying-Chun; Ghasemzadeh, Ali; Kochel, Christina; Nirschl, Thomas; Francica, Brian; Lopez-Bujanda, Zoila; Carrera Haro, Maria; Tam, Ada; Anders, Robert; Selby, Mark; Korman, Alan; Drake, Charles
Abstract Background Immune checkpoint blockade has shown promising antitumor activity against a variety of tumor types. However, responses in castration-resistant prostate cancer remain relatively rare—potentially due to low baseline levels of infiltration. Using an immunocompetent cMyc-driven model (Myc-CaP), we sought to understand the immune infiltrate induced by androgen deprivation therapy (ADT) and to leverage that infiltration toward therapeutic benefit. Methods Using flow cytometry, qPCR and IHC, we quantified ADT-induced immune infiltration in terms of cell type and function. Preclinical treatment studies tested the combinatorial effects of ADT and immune checkpoint blockade using tumor outgrowth and overall survival as end points. Results ADT induces a complex pro-inflammatory infiltrate. This pro-inflammatory infiltrate was apparent in the early postcastration period but diminished as castration resistance emerged. Combining ADT with tumor-infiltrating regulatory T cell (Treg) depletion using a depleting anti-CTLA-4 antibody significantly delayed the development of castration resistance and prolonged survival of a fraction of tumor-bearing mice. Immunotherapy as a monotherapy failed to provide a survival benefit and was ineffective if not administered in the peri-castration period. Conclusions The immune infiltrate induced by ADT is diverse and varies over time. Therapeutic strategies focusing on depleting Tregs in the peri-castration period are of particular interest.